2017
DOI: 10.1088/2053-1583/aa8ab5
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation and growth of WSe 2 : enabling large grain transition metal dichalcogenides

Abstract: The limited grain size (<200 nm) for transition metal dichalcogenides (TMDs) grown by molecular beam epitaxy (MBE) reported in the literature thus far is unsuitable for high-performance device applications. In this work, the fundamental nucleation and growth behavior of WSe 2 is investigated through a detailed experimental design combined with on-lattice, diffusion-based first principles kinetic modeling to enable large area TMD growth. A three-stage adsorption-diffusion-attachment mechanism is identified and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
134
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(144 citation statements)
references
References 69 publications
9
134
1
Order By: Relevance
“…MBE utilizes ultra-pure sources which are heated in effusion cells, resulting in "beams" of atoms or molecules, which are then deposited on a heated substrate (Figure 3c). 87 The lower temperature growths in MBE also help in minimizing chalcogen vacancies and intermixing of layers during the growth of vertical heterostructures, which are common problems associated with high temperature growths in P-CVD and gas source CVD. MBE growth of transition metal dichalcogenides was investigated prolifically by Koma beginning in the 1980s.…”
Section: Milestonesmentioning
confidence: 99%
“…MBE utilizes ultra-pure sources which are heated in effusion cells, resulting in "beams" of atoms or molecules, which are then deposited on a heated substrate (Figure 3c). 87 The lower temperature growths in MBE also help in minimizing chalcogen vacancies and intermixing of layers during the growth of vertical heterostructures, which are common problems associated with high temperature growths in P-CVD and gas source CVD. MBE growth of transition metal dichalcogenides was investigated prolifically by Koma beginning in the 1980s.…”
Section: Milestonesmentioning
confidence: 99%
“…It was found that the fast kink nucleation and propagation, rather than edge attachment and diffusion, could lead to ultrafast growth of monolayer WSe 2 168 . KMC simulations also guided CVD growth of large-scale WSe 2 grains by controlling the three-stage adsorption-diffusion-attachment mechanisms 169 . KMC model is also a key component in a more generalized mechanistic model for growth morphology predictions of 2D materials 47 .…”
Section: Mesoscale Simulationsmentioning
confidence: 99%
“…Best specimens of S-TMD monolayers are usually obtained by the mechanical exfoliation of bulk (natural or synthetic) crystals which leads to micrometer sized flakes, suitable for scientific investigations or for demonstrating a) Electronic mail: clement.faugeras@lncmi.cnrs.fr prototype devices, but preventing their use in realistic applications produced at an industrial scale. Growth techniques, mainly chemical vapor deposition (CVD) 17 and molecular beam epitaxy (MBE) 18,19 , have been developed to produce large scale monolayers of S-TMD suitable for electronics and optoelectronics applications, or to elaborate vertical/horizontal heterostructures 20,21 . In this letter, we demonstrate CVD grown S-TMD monolayers with optical quality comparable to state of the art exfoliated flakes.…”
mentioning
confidence: 99%